Pengaruh Fasilitas Kesehatan dan Kinerja terhadap Kepuasan Pasien melalui Kualitas Pelayanan di Ruang Kebidanan RS.Cut Meutia Medika Nusantara Kota Langsa - Nurrahmani Nurrahmani; Nurhidayati Nurhidayati; Hanafi Nasution (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Healthcare is an integral part of health development in Indonesia, which aims to optimally improve public health. Hospitals, as healthcare facilities, are required to provide quality, safe, and patient-centered services. Service quality is a key indicator of service success, as good service impacts patient satisfaction. One of the most important services in hospitals is obstetrics, which directly relates to maternal and infant health, making patient satisfaction a crucial aspect. Midwives, as professional healthcare workers, play a strategic role in providing comprehensive, sustainable, and patient-centered midwifery care. This study aims to analyze the influence of healthcare facilities and midwife performance on patient satisfaction through service quality. The method used is a quantitative study with an analytical approach and a cross-sectional design. The results of the multiple linear regression test indicate that midwife performance has a more dominant influence on service quality than healthcare facilities. Meanwhile, regarding patient satisfaction, service quality is the most dominant factor, followed by midwife performance and healthcare facilities. The conclusion of this study is that service quality reflects the overall patient experience and is a key factor in improving patient satisfaction.